Traditional Chinese medicine and plant-derived bioactive compounds as sustainable alternatives to antibiotics in bovine mastitis: a review - Fan, Xuewei; Qadeer, Abdul; Asiri, Mohammed; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Alsharif, Khalaf F.; Khan, Muhammad Zahoor; Jiang, Xin (Frontiers in Veterinary Science, 2025)
Bovine mastitis, an inflammatory condition of the mammary glands caused by diverse etiological agents, represents a significant economic challenge to the global dairy industry, resulting in annual losses of approximately $35 billion. While antibiotic therapy remains the conventional intervention for both prophylaxis and treatment, the increasing prevalence of antimicrobial resistance (AMR), particularly the emergence of multidrug-resistant and methicillin-resistant strains, has compromised therapeutic efficacy. These developments pose substantial concerns regarding milk safety and public health implications. Consequently, research attention has shifted toward alternative therapeutic modalities, encompassing phytotherapeutic interventions, nutritional modifications, and traditional Chinese medicine (TCM). Numerous plant species demonstrate significant antimicrobial properties while maintaining favorable safety profiles for humans, animals, and ecological systems. Complementary therapeutic approaches, including acupuncture and traditional herbal formulations, have exhibited promising potential in enhancing treatment outcomes and improving milk quality parameters. This review synthesizes current evidence on the integration of traditional Chinese medicine and plant-derived bioactive compounds into sustainable, holistic strategies for mastitis management, with implications for animal welfare, economic sustainability, and public health safety.